Electronic comparison of InAs wurtzite and zincblende phases using nanowire transistors - Ullah, A; Joyce, H; Burke, A; Wong-Leung, J; Tan, H; Jagadish, C; Micolich, A (2013)
We compare the electronic characteristics of nanowire field-effect transistors made using single pure wurtzite and pure zincblende InAs nanowires grown from identical catalyst particles. We compare the transfer characteristics and field-effect mobility versus temperature for these devices to better understand how differences in InAs phase govern the electronic properties of nanowire transistors. © 2013 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.